DETERMINANTS OF DIVIDEND PAYOUT POLICY: EVIDENCE FROM LQ-45 COMPANIES - Deliana, Hedianti
Dividend payout policy determines the decision of the dividend distribution to the shareholders is an important issue for both the investor and the firm. However, dividend payout policy has become of the most controversial and the most debatable issues in the corporate finance literature and still kep its prominent place both in developed and emerging markets. Therefore, this research aims to identify the determinants of dividend payout policy in LQ 45 index firms, since this price index is one of the most attractive among other index in Indonesia. This research employed Dividend Payout Policy as measured by Dividend per Share as the dependent variable. Meanwhile the independent variable which are Leverage as measured by Debt to Asset Ratio, Liquidity as measured by Current Ratio, Profitability as measured by Return on Equity, and Firm Size as measured by Total Asset. The sample of this research is taken using purposive sampling. The sample consist of 19 companies listed in LQ 45 index for period February - July 2019 with time horizon from 2008 to 2019, thus the number of observation point is 190. Panel data regresson is applied to analyze the data due to the combination of the data which consist od cross-section and time-series. Unit root test for stationary followed by classical assumption test is held before running the regression. Afterwards, Lagrange-Multiplier Test, Chow Test, and Hausman Test is conducted to determine the suitable approach for estimation model which resulted in the Fixed Effect Model approach. T-test and F-test with confidence interval of 95% or alpha (?) 5% is conducted to test the hypothesis. The data analysis is done by using Stata 14.2 statistical software. T-test result shows that there are significant positive relationship between profitability and firm size towards dividend payout policy. This implies that LQ-45 firms with higher profitability and larger firm size tend to distribute more dividend. F-test result shows that all independent variables significantly affect dividend payout policy. Adjusted R2 value of the model is 0.8569 which indicates that 85.69% of variability in the dependent variable can be explained by the independent variables while the remaining 14.31% is explained by other variables which are not included in this research. Based on the findings of this research, potential investors are suggested to pay more attention to firm’s profitability and firm’s size of LQ 45 index before investing in the company. While for the management, it is suggested to maintain the level for firm’s profitability and firm’s size in order to deliver the suitable signal to the investors. For the future research, it is suggested to add new variables aside from the independent variable to increase the adjusted R2 value